Epibrassinolide Regulates Lhcb5 Expression Though the Transcription Factor of MYBR17 in Maize - Hui Li; Xuewu He; Huayang Lv; Hongyu Zhang; Fuhai Peng; Jun Song; Wenjuan Liu; Junjie Zhang (Biomolecules)
Photosynthesis, which is the foundation of crop growth and development, is accompanied by complex transcriptional regulatory mechanisms. Research has established that brassinosteroids (BRs) play a role in regulating plant photosynthesis, with the majority of research focusing on the physiological level and regulation of rate-limiting enzymes in the dark reactions of photosynthesis. However, studies on their effects on maize photosynthesis, specifically on light-harvesting antenna proteins, have yet to be conducted. The peripheral light-harvesting antenna protein Lhcb5 is crucial for capturing and dissipating light energy. Herein, by analyzing the transcriptomic data of maize seedling leaves treated with 24-epibrassinolide (EBR) and verifying them using qPCR experiments, we found that the MYBR17 transcription factor may regulate the expression of the photosynthetic light-harvesting antenna protein gene. Further experiments using protoplast transient expression and yeast one-hybrid tests showed that the maize transcription factor MYBR17 responds to EBR signals and binds to the promoter of the light-harvesting antenna protein Lhcb5, thereby upregulating its expression. These results were validated using an Arabidopsis mybr17 mutant. Our results offer a theoretical foundation for the application of BRs to enhance the photosynthetic efficiency of maize.